Deposit interest rate pass-through in Central and Eastern European countries before and after 2021 - Gábor Hajnal; Bálint Dancsik; Zsuzsanna Hosszú; Ákos Attila Ozoróczy (Central Bank Review, 2025)
The study analyzes interest rate pass-through for household and corporate deposits in specific markets in the Central and Eastern European (CEE) region, with a focus on the tightening cycle that began in mid-2021. This period is of particular interest to monetary policy, as sharp rate hikes by central banks, in response to a high inflationary environment, followed a period characterized by an abundance of liquidity. We examine the relationship between interbank and deposit interest rates using two methods: wavelet transform and error-correction model. Based on the wavelet analysis, we found a weakening of pass-through and a slowdown in the repricing of deposit interest rates during the tightening cycle across the countries of the CEE region, particularly in the household segment. Using error-correction models, we observe a consistent weakening in both the degree and speed of interest rate pass-through in the Hungarian and Polish deposit markets during the tightening cycle. The extent of pass-through declined most in the Hungarian household deposit market among all CEE countries.